Pharmacokinetics and safety of TCMCB07, a melanocortin‐4 antagonist peptide in dogs - Axiak‐Bechtel, Sandra M. (Pharmacol Res Perspect, 2021)
The melanocortin‐4 receptor (MC4R) antagonistic peptide TCMCB07 was developed for the treatment of cachexia. The objectives of this study were to examine pharmacokinetics and safety of TCMCB07 administered subcutaneously to healthy dogs. Dogs were treated with high‐ (2.25 mg kg(−1)) (n = 5) and low‐dose TCMCB07 (0.75 mg kg(−1)) (n = 5) once daily for 28 days with a 14‐day washout period between groups. Histamine levels, complete blood count, chemistry panel, blood pressure, 24‐hour Holter recording, and pharmacokinetic parameters were monitored in the high‐dose group. Physical examination changes were limited to weight gain and darkening of the coat color. There was no elevation of plasma histamine within 24 hours of injection but there was a significant elevation of plasma histamine across time. An approximately doubled eosinophil count and an approximately 25% increase, and then 25% decrease back to pre‐treatment plasma phosphorous were also found, although both remained within the reference interval. Serial blood pressure and 24‐hour Holter monitors revealed no clinically relevant changes. A difference was found in the AUC between dosing groups and a significant effect of dose, time, and interaction was noted for V(d). Low‐dose TCMCB07 had a C(max) of 2.1 ug ml(−1) at day 28, compared to high‐dose TCMCB07 which had a C(max) 3.6 ug ml(−1) at day 28. Once‐daily subcutaneous administration of TCMCB07 was well‐tolerated for up to 28 days in dogs when administered at doses one and three times (0.75 mg kg(−1) and 2.25 mg kg(−1)) the predicted therapeutic dose and pharmacokinetic parameters are described. SIGNIFICANCE STATEMENT: Melanocortin‐4 receptor (MC4R) antagonistic peptide TCMCB07 is safe at both low and high doses in dogs. Therapy was tolerated well as determined by physical examination, clinical pathology, and cardiovascular parameters; darkening of the coat was noted with treatment and resolved with discontinuation. Pharmacokinetics are described and further study in the naturally occurring canine model is warranted.